(3HdhZ GdeCQH aj CNHGQ GdYbQHs - (3YHO GdQMef Hf CHj HcQ Hf eMeO GdNVjQj GdSjhWj, CHh GdaVd , LdGd GdOjf , J (B911 (3g`s
(3ChdgG (B:s
(3gPG LRA ef CNHGQ GdYbQH jSei HdhZ GdeCQH ai CNHGQ GdYbQH PcQ CSeGFgG GdYbQH ddPcQ hGdCfKi hGdLeY YbGQH s
(3BNQgG (B:s
(3BNQ HdhZ GdeCQH ai CNHGQ GdYbQH JCdja GdMGaX LdGd GdOjf GdSjhWi QMeg Gddg JYGdi Bejf s
(3bWYJGfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B254s
(3eUOQ GbJfGA GdCUd (B:s
(3GdQHGW (B(1027(3d(B) s
Keywords: (3GdeYGQa GdYGeIs